Chemical and Oxygen Isotopic Composition of Roman and Late Antique Glass from Northern Greece - Alberta Silvestri; Elissavet Dotsika; Antonio Longinelli; Enricomaria Selmo; Sophia Doukata-Demertzi (Journal of Chemistry)
The present paper emphasizes the importance of measuring the oxygen isotopic and chemical compositions of ancient glass, in order to constrain some features such as age, raw materials, and production technologies and to identify the “fingerprint” of local productions. In this context, thirty-nine Roman and late Antique glass samples and eight chert samples from northern Greece were selected and analysed for their oxygen isotopic and chemical compositions. Results show that the majority of glass samples are produced using natron as flux and have δ18O values of about 15.5‰, plus or minus a few tenths of one per mil, suggesting that raw materials probably come from Levantine area. Four samples are heavily enriched in 18O, and their chemical composition clearly shows that they were made with soda plant ash as flux. Isotopic and chemical data of Greek chert samples support the hypothesis of local production of the above samples. About half of the glass samples have chemical compositions, which allow their age to be constrained to the late Antique period. For the remaining glass, similarities with literature compositional groups are reported and discussed.